PENGEMBANGAN INSTRUMEN PENILAIAN AUTENTIK BERBASIS MICROSOFT FORM PADA MATERI SISTEM PEREDARAN DARAH MANUSIA - Ferini, Devy; Rokhman, Fathur; Suminar , Tri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The implementation of authentic assessment in Biology learning, particularly on the topic of the human circulatory system, still encounters various challenges. Teachers commonly focus on cognitive aspects using traditional approaches, while students’ psychomotor skills tend to be overlooked. Constraints such as limited time, large class sizes, and the lack of practical assessment instruments hinder the optimal application of authentic assessment. On the other hand, developments in educational technology offer potential solutions through digital platforms like Microsoft Forms. This study aims to develop a Microsoft Forms–based authentic assessment instrument on the topic of the human circulatory system to measure students' psychomotor skills. Employing a modified Borg & Gall development model, the instrument was tested for its validity and reliability, and then used to assess Grade XI students at MAN Insan Cendekia OKI. The results indicate that the instrument is valid, reliable, and capable of illustrating students' psychomotor profiles within the Kurikulum Merdeka learning framework. This instrument presents an innovative alternative to support the implementation of Kurikulum Merdeka, which emphasizes holistic and meaningful assessment.